Effect of telemetric monitoring in the first 30 days of continuous positive airway pressure adaptation for obstructive sleep apnoea syndrome – a controlled pilot study. (June 2016) - Frasnelli, Matthias; Baty, Florent; Niedermann, Jolanda; Brutsche, Martin H; Schoch, Otto D
Obstructive sleep apnoea syndrome (OSAS) is characterised by repetitive collapse of the upper airway during sleep. Continuous positive airway pressure (CPAP) applied via a mask is the standard treatment for OSAS. CPAP adherence is crucial in therapy to prevent the deleterious consequences of OSAS. We hypothesised that a combination of supervision by telemetry together with targeted telephone support in the first month of CPAP would increase CPAP adherence and treatment success. A total of 113 OSAS patients followed by telemetry-triggered interventions used the device for 5.3 h/night on 28/30 nights, significantly more than the 110 OSAS patients in the control group with 4.6 h/night and 27/30 nights. Telemetry-triggered interventions have a significant impact on adherence rate in early CPAP treatment. These results can be reached with an acceptable additional effort.